Influence of the pre-storage treatment method and storage parameters on the organoleptic quality indicators of carrot and beet roots - T. V. Pershakova; E. Y. Panasenko; S. M. Gorlov; V. N. Aleshin (Новые технологии)
Preservation of commercial quality and nutritional value of crop production is one of the most important and most relevant areas of research for scientists working in the interests of the agro-industrial complex. The article presents the results of studying the influence of the method of pre-storage processing and storage parameters on the organoleptic quality parameters of carrot and beet roots. The objects of the study were the carrot root of Abaco table variety and the beet root of the Ronda variety. The root crops were treated with extremely low frequency electromagnetic fields and Vitaplan and Bactofit biopreparations before storage. After the treatment, the roots were stored at +2±1°С for 56 days and +25±1°С for 21 days. Evaluation of quality indicators was carried out using a scoring organoleptic scale for the following indicators: shape, appearance, color, smell, taste, freshness, integrity. As a result of the research, it has been established that the total score of the organoleptic evaluation of the root crops subjected to pre-treatment is higher compared with the control in all experiments. Integrated treatment of roots with extremely low frequency electromagnetic fields and biological preparations has proved to be a processing method that ensures the highest preservation of root crops quality.